A Grid-Connected Photovoltaic Interface System for Delivering Active and Reactive Powers - Neilcy T Mooniarsih; Syafrudin Masri; Mohd Hafeez; Ayong Hiendro (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper presents a grid-connected photovoltaic (PV) interface for delivering both active and reactive powers. The PV interface employs H-bridge topology DC-DC converter and inverter with analog control technology. The power flow is controlled solely by the adjustable DC output voltage of the DC to DC converter. In order to evaluate the PV interface system’s performances, it is tested by delivering power to the grid with low pawer factor. The experimental results show that at 300W active load, the inverter could deliver the reactive power of 400VAR. The PV interface could also produce very low harmonic voltage and current distorsions. The laboratory measurements show that the total harmonic distortions of inverter output voltage and current are 0.46% and 0.05%, respectively